The Effectiveness of Implementation and Compliance with ICCPR in the Case of Violations of the Right to Life and the Right to be Free from Tortured in Syria - Mentari Jastisia (Tirtayasa Journal of International Law, 2022)
ABSTRACT The case of Syria is closely related to the civil and political rights of its citizens, the Syrian Government has violated the civil and political rights of its citizens, namely the violation of the right to life and the right to be free from torture. But as a member of the United Nations, Syria has ratified the ICCPR on 21 April 1969. ICCPR basically contains provisions on restrictions on use Authority by the state's repressive apparatus. The approach method used in this research is normative juridical which focuses on research on applicable legal provisions, namely on How’s the Effectiveness of Implementation and Compliance with the International Covenant on Civil and Political Rights (ICCPR) in the Case of Violations of the Right to Life and the Right to be free from tortured in Syria. The specification of this research is descriptive analysis by showing the lack of legal protection in the field of Syrian immigrants and then conducting an analysis with various related legal sources. Syria as a member country of the ICCPR has carried out its obligations by sending periodic reports on cases of civil and political rights violations in Syria that are likely to experience delays. Syria has not yet ratified Optional Protocol I, so Syria can not be adapted by other ICCPR member states on the rights and politics in Syria, nor can there be any individual complaints by the Syrians against cases of civil and political rights. The author also concludes that in view of recent cases in Syria, it can be said that it violates the provisions of Article 6 & 7 ICCPR.Keywords; ICCPR; Right to Life; Rights to be Free; Syria